2019
DOI: 10.4252/wjsc.v11.i11.990
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating liver fibrosis in an animal model using the secretome released from miR-122-transfected adipose-derived stem cells

Abstract: BACKGROUNDRecently, the exclusive use of mesenchymal stem cell (MSC)-secreted molecules, called secretome, rather than cells, has been evaluated for overcoming the limitations of cell-based therapy, while maintaining its advantages. However, the use of naïve secretome may not fully satisfy the specificity of each disease. Therefore, it appears to be more advantageous to use the functionally reinforced secretome through a series of processes involving physico-chemical adjustments or genetic manipulation rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…ASCs were plated into culture flask in Dulbecco’s Modified Eagle Medium with low glucose (DMEM/low glucose; Hyclone, Logan, UT, USA) supplemented with 0.1 mg/mL of streptomycin (Gibco BRL, Carlsbad, CA, USA), 100 U/mL of penicillin (Gibco), 10% fetal bovine serum (FBS; Hyclone) at 37°C in humidified chamber containing 5% carbon dioxide [ 8 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ASCs were plated into culture flask in Dulbecco’s Modified Eagle Medium with low glucose (DMEM/low glucose; Hyclone, Logan, UT, USA) supplemented with 0.1 mg/mL of streptomycin (Gibco BRL, Carlsbad, CA, USA), 100 U/mL of penicillin (Gibco), 10% fetal bovine serum (FBS; Hyclone) at 37°C in humidified chamber containing 5% carbon dioxide [ 8 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 24 hours, ASCs were refed serum-free DMEM/low glucose for 24 hours. Then, the secretome was obtained 200 µL amount at ASCs, the CM were concentrated by 25 fold, by ultrafiltration device with a 3-kDa cutoff (Amicon Ultra-15; Millipore, Bedford, MA, USA) [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lou et al showed that miR-122 modified adipose tissue-derived MSCs (AMSC-122), which were constructed through lentivirus-mediated transfer of pre-miR-122, more effectively inhibited the proliferation of hepatic stellate cells (HSCs) and the maturation of collagen [45]. In the latest study, the secreted proteome released from AMSC-122 has higher antifibrotic and antiinflammatory properties than the pure secreted proteome [46]. The research by Chen et al reported that inhibition of miR-26a-5p can further improve the therapeutic effect of MSCs on liver cirrhosis through increasing the expression of HGF protein in MSCs [47].…”
Section: Gene Modification Enhances the Therapeutic Effects Ofmentioning
confidence: 99%
“…miRNAs have been reported to be deregulated in various human diseases and involved in many biological processes such as cell proliferation ( Ma et al, 2018 ; Bruch et al, 2019 ). Currently, a growing body of evidence suggests that miRNAs participate in the control of hepatic stellate cell (HSC) activation, which is an essential event in liver fibrosis ( Kim et al, 2019 ). We previously found that miR-17-5p, up-regulated in activated HSCs, promotes HSC activation via targeting of smad7 ( Yu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%